Museums in the digital age changing meanings of place, community, and culture - Bautista, Susana Smith 1966- (AltaMira Press, 2014)
Museums in the Museums in the Digital Age: Changing Meanings of Place, Community, and Culture first provides a theoretical framework of how the critical notions of place, community, and culture are changing in the digital age, respective to the field of museology.